2020
DOI: 10.1111/gtc.12764
|View full text |Cite
|
Sign up to set email alerts
|

miR‐29c‐3p inhibits microglial NLRP3 inflammasome activation by targeting NFAT5 in Parkinson's disease

Abstract: Microglial inflammation is identified as a key process associated with Parkinson's disease (PD) pathogenesis. Our previous study showed that miR-29c-3p (miR-29c) exhibited anti-inflammatory properties in PD animal and neuronal models. However, the specific role and regulatory mechanism of miR-29c played in microglia are still unclear. In this study, lipopolysaccharide (LPS)-stimulated BV-2 cells were used to establish a cellular model of microglial activation for investigating PD. The results showed a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…43,44 A number of studies suggest that NFAT5 can be activated by inflammatory stimuli induction and participates in neuroinflammation. 45,46 Furthermore, NFAT5 increased the expression of the M1-polarized macrophages characteristic genes to support the pro-inflammatory function of macrophages. 40 Thus, miR-146a-5p alleviated ICH-induced brain injury, potentially via direct inhibition of NFAT5.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 A number of studies suggest that NFAT5 can be activated by inflammatory stimuli induction and participates in neuroinflammation. 45,46 Furthermore, NFAT5 increased the expression of the M1-polarized macrophages characteristic genes to support the pro-inflammatory function of macrophages. 40 Thus, miR-146a-5p alleviated ICH-induced brain injury, potentially via direct inhibition of NFAT5.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-29c-3p, which acts as a biomarker, was reduced in patients with Alzheimer's disease (40). Moreover, the overexpression of miR-29c-3p suppressed proinflammatory cytokine release in LPS-stimulated BV-2 cells with anti-inflammatory properties (21), revealed that miR-29c-3p A B FIGURE 6 | NFAT5 was a direct binding target of miR-29c-3p. (A) The binding sites of NFAT5 and miR-29c-3p.…”
Section: Discussionmentioning
confidence: 96%
“…Nuclear factor of activated T cell 5 (NFAT5) expression was assessed using the western blot assay, as previously described (21). Briefly, CTX-TNA2 cells were harvested and lysed in RIPA buffer (Beyotime, Shanghai, China).…”
Section: Western Blotmentioning
confidence: 99%
“…Furthermore, miR-29c exhibited anti-inflammatory properties by ameliorated the elevated pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) and apoptosis in the MPTPtreated mice (Wang et al, 2020b). Additionally, over-expression of miR-29c suppressed the LPS-induced microglial activation, via modulation of NOD-like receptor protein 3 (NLRP3) inflammasome by targeting nuclear factor of activated T-cells (NFAT) 5 (Wang et al, 2020a).…”
Section: Mir-29cmentioning
confidence: 99%